Adherence to Treatment Regimen among Type 2 Diabetics at the Ridge Hospital, Accra. - Kwakye, B. (University Of Ghana, 2016)
Diabetes mellitus is a chronic disease that occurs when the pancreas is no longer able to produce insulin, or when the body cannot make good use of the insulin it produces. There are three main types of diabetes. The most common type is the Type 2 diabetes which represents 90% of cases worldwide .The other types of diabetes are Type 1 diabetes and gestational diabetes. Type 2 diabetics are faced with challenges and experiences such as financial difficulties, forgetfulness, and problems taking the medication, stigmatization, depression and anxiety. These experiences hinder their ability to adhere to treatment. The study seeks to explore the factors that influence treatment adherence at the Ridge Hospital in Accra. An exploratory descriptive research design was used for the study. Fourteen participants were recruited from December 2015 – March 2016. Interviews were conducted in the English and Twi languages. Interviews conducted in the local language were translated into the English afterwards. Data was analyzed using thematic content analysis. The study identified some factors that influence treatment adherence. These include knowledge of the diabetes, complications to avoid, efforts to improve the condition and benefits of adherence. It also identified some barriers to adherence such as forgetfulness, difficulty taking medication, depression, anxiety, stigma, blindness, amputation and others. The study recommended ways that health providers could employ to intensify patient education on each visit. This education would be holistic in order to increase the rate of adherence by the people living with diabetes. Future research into adherence to treatment regimen among diabetics which looks at the health providers‟ perspective can be carried out.
Thesis (MPhil.)
Keywords: Diabetics; Chronic Disease; Insulin; Ghana